Rethinking Organizations and Society from an Ethical Perspective - Chanlat, Jean-Francois (Organizações & Sociedade, 2022)
Contemporary organizations and societies have witnessed a return of ethical issues for several decades – with the ecological issue occupying center stage among its many contributing factors. In fact, the current Anthropocene era requires urgent ethics-based appropriate action. In this article, after recalling the meaning of ethics, we discuss how ethics is associated with many capacities, and how an ethics of finitude can aid organizations and societies put into practice a true sustainable development, which is now indispensable for our collective survival. From this ethical perspective, we invite individuals, citizens, organizations, societies, and the world to enact social radical change.